Activation-Induced TIM-4 Expression Identifies Differential Responsiveness of Intestinal CD103+ CD11b+ Dendritic Cells to a Mucosal Adjuvant - Hilligan, Kerry L. (PLoS One, 2016)
Macrophage and dendritic cell (DC) populations residing in the intestinal lamina propria (LP) are highly heterogeneous and have disparate yet collaborative roles in the promotion of adaptive immune responses towards intestinal antigen. Under steady-state conditions, macrophages are efficient at acquiring antigen but are non-migratory. In comparison, intestinal DC are inefficient at antigen uptake but migrate to the mesenteric lymph nodes (mLN) where they present antigen to T cells. Whether such distinction in the roles of DC and macrophages in the uptake and transport of antigen is maintained under immunostimulatory conditions is less clear. Here we show that the scavenger and phosphatidylserine receptor T cell Immunoglobulin and Mucin (TIM)-4 is expressed by the majority of LP macrophages at steady-state, whereas DC are TIM-4 negative. Oral treatment with the mucosal adjuvant cholera toxin (CT) induces expression of TIM-4 on a proportion of CD103+ CD11b+ DC in the LP. TIM-4+ DC selectively express high levels of co-stimulatory molecules after CT treatment and are detected in the mLN a short time after appearing in the LP. Importantly, intestinal macrophages and DC expressing TIM-4 are more efficient than their TIM-4 negative counterparts at taking up apoptotic cells and soluble antigen ex vivo. Taken together, our results show that CT induces phenotypic changes to migratory intestinal DC that may impact their ability to take up local antigens and in turn promote the priming of mucosal immunity.